Cape Verde : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Cape Verde's Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Cape Verde's economic and policy performance is largely on track vis-a-vis the PRGF objectives. All quantitative and structural performance criteria for end-June 2004 and all indicative targets for end-September 2004 were observed, as were all but three structural benchmarks. Of these three, one has now been met and the authorities are making progress toward complying with the other two. GDP growth of 4 percent is now expected in 2004.